"Who Will Marry a Diseased Girl?" Marriage, Gender, and Tuberculosis Stigma in Asia. (July 2019) - Hatherall, Bethan; Newell, James N.; Emmel, Nick; Baral, Sushil Chandra; Khan, Muhammad Amir
In a qualitative study on the stigma associated with tuberculosis (TB), involving 73 interviews and eight focus groups conducted in five sites across three countries (Bangladesh, Nepal, and Pakistan), participants spoke of TB's negative impact on the marriage prospects of women in particular. Combining the approach to discovering grounded theory with a conceptualization of causality based on a realist ontology, we developed a theory to explain the relationships between TB, gender, and marriage. The mechanism at the heart of the theory is TB's disruptiveness to the gendered roles of wife (or daughter-in-law) and mother. It is this disruptiveness that gives legitimacy to the rejection of marriage to a woman with TB. Whether or not this mechanism results in a negative impact of TB on marriage prospects depends on a range of contextual factors, providing opportunities for interventions and policies.